Sociology of religion: Joachim Wach's brilliant synthesis of theological, anthropological and sociological studies on te interrelation of religian and sciety - Joachim Wach (Chicago Press, 1944)
oen, c.1-4,ws.c.5-6/ast c.7/ws.c.8